Imaging the Antistaphylococcal Activity of CATH-2: Mechanism of Attack and Regulation of Inflammatory Response - Viktoria A. F. Schneider (American Society for Microbiology, 2017)
ABSTRACT Chicken cathelicidin-2 (CATH-2) is a broad-spectrum antimicrobial host defense peptide (HDP) that may serve as a paradigm for the development of new antimicrobial agents. While previous studies have elucidated the mechanism by which CATH-2 kills Escherichia coli, its mode of action against Gram-positive bacteria remains to be determined. In this study, we explored the underlying antibacterial mechanism of CATH-2 against a methicillin-resistant strain of Staphylococcus aureus and the effect of CATH-2-mediated S. aureus killing on immune activation. Visualization of the antimicrobial activity of CATH-2 against S. aureus with live-imaging confocal microscopy demonstrated that CATH-2 directly binds the bacteria, which is followed by membrane permeabilization and cell shrinkage. Transmission electron microscopy (TEM) studies further showed that CATH-2 initiated pronounced morphological changes of the membrane (mesosome formation) and ribosomal structures (clustering) in a dose-dependent manner. Immunolabeling of these sections demonstrated that CATH-2 binds and passes the bacterial membrane at subminimal bactericidal concentrations (sub-MBCs). Furthermore, competition assays and isothermal titration calorimetry (ITC) analysis provided evidence that CATH-2 directly interacts with lipoteichoic acid and cardiolipin. Finally, stimulation of macrophages with S. aureus and CATH-2 showed that CATH-2 not only kills S. aureus but also has the potential to limit S. aureus-induced inflammation at or above the MBC. Taken together, it is concluded that at sub-MBCs, CATH-2 perturbs the bacterial membrane and subsequently enters the cell and binds intracellular S. aureus components, while at or above the MBC, CATH-2 causes disruption of membrane integrity and inhibits S. aureus-induced macrophage activation. IMPORTANCE Due to the high use of antibiotics in both human and veterinary settings, many bacteria have become resistant to those antibiotics that we so heavily rely on. Methicillin-resistant S. aureus (MRSA) is one of these difficult-to-treat resistant pathogens for which novel antimicrobial therapies will be required in the near future. One novel approach could be the utilization of naturally occurring antimicrobial peptides, such as chicken CATH-2, which have been show to act against a wide variety of bacteria. However, before these peptides can be used clinically, more knowledge of their functions and mechanisms of action is required. In this study, we used live imaging and electron microscopy to visualize in detail how CATH-2 kills S. aureus, and we investigated how CATH-2 affects immune activation by S. aureus. Together, these results give a better understanding of how CATH-2 kills S. aureus and what the potential immunological consequences of this killing can be.